1996
DOI: 10.1093/oxfordjournals.molbev.a025628
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a vitellogenin gene between two distantly related rhabditid nematode species

Abstract: Three vitellogenin genes from the free-living nematode Caenorhabditis elegans have previously been characterized at the molecular level. In order to study evolutionary relationships within this poorly understood taxon, we have cloned a vitellogenin gene, CEW1-vit-6, from a distantly related species belonging to the same family as C. elegans. Screening of a genomic library with a probe to total poly(A+) RNA yielded three clones that hybridized more intensely than all others, and all three corresponded to a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
14

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 43 publications
1
24
0
14
Order By: Relevance
“…We have begun to answer this question by identifying both a conserved operon and SL2 transsplicing in another free-living nematode, Dolichorhabditis. Dolichorhabditis is a free-living rhabditid nematode belonging to the same family as C. elegans (36,41). Although the two species are morphologically similar, C. elegans 28S rRNA differs from Dolichorhabditis 28S rRNA at 48 of 241 positions (K. Thomas, personal communication).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have begun to answer this question by identifying both a conserved operon and SL2 transsplicing in another free-living nematode, Dolichorhabditis. Dolichorhabditis is a free-living rhabditid nematode belonging to the same family as C. elegans (36,41). Although the two species are morphologically similar, C. elegans 28S rRNA differs from Dolichorhabditis 28S rRNA at 48 of 241 positions (K. Thomas, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Although the two species are morphologically similar, C. elegans 28S rRNA differs from Dolichorhabditis 28S rRNA at 48 of 241 positions (K. Thomas, personal communication). Comparison of the C. elegans and Dolichorhabditis vit-6 genes demonstrates that whereas the primary structure of the encoded protein is related, it is so distant that even its codon usage and intron positions are quite different (36). Recently, an analysis of the 18S rRNA from Dolichorhabditis showed that it is a rhabditid species, most closely related to the parasitic strongylids (M. Blaxter, P. DeLey, L. Liu, and J. Garey, personal communication).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several analyses based on the conserved N-terminal regions of Vtgs revealed a closer relationship between the Vtgs from nematodes and insects compared with Vtgs from vertebrates (61,68). In contrast, other analyses suggest a closer relationship between the Vtgs from nematodes and vertebrates compared with Vtgs from insects (4,(71)(72)(73). The difference between the two groups of analyses may be explained by the fact that the Vtg trees were unrooted (73), rooted using an insect Vtg rather than a non-Vtg LLTP (72), or interpreted without taking the included apoB outgroup into account (4,73).…”
Section: Three Families Of Lltpsmentioning
confidence: 99%